(untitled) (Portuguese Journal of Family Medicine and General Practice, 2011)
Atopic dermatitis is a chronic relapsing inflammatory skin condition, of increasing incidence. Strict collaboration between the specialities that deal with this illness is essential. The epidemiology, aetiology and pathogenesis of atopic dermatitis will be briefly approached; the clinical features of the disease and some practical aspects of its treatment will be addressed.